Sacramento Valley Ultra Mafic Soils and Air Samples as Potential Health Hazards - Fahrenkrog, Brooke (My University, 2010)
The Sacramento Valley in California is bordered by two mountain ranges; the Coast Ranges and the Sierra Nevadas. Both ranges contain extensive exposures of ophiolites now exposed as serpentenites. These ophiolites are remnants of a mid-Jurassic accretionary wedge which attached slivers of ocean crust and mantle to the continental edge. The ophiolites contain high concentrations of chromium (Cr) and nickel(Ni). TEM is one of the only instruments able to analyze both the chemistry and crystalline structure of minerals that are less than one micron in size and is capable of analysis in the nano-particulate size range. UW-Eau Claire collaborated with the USGS to study the chemistry of both the fine grained fraction of the soil and particulates collected on air filters from soil samples.
Color poster with text, images, and maps.
Keywords: Geology--California--Sacramento Valley; Soils--Trace element content--Sacramento Valley; Soils--Trace element content--Measurement; Air--Pollution--California--Sacramento Valley; Air--Pollution--Measurement; Sacramento Valley (Calif.)--Environmental conditions; Posters